We want to find the expression that represent the given pattern.
To determine this let us substitute 2 into each expression, the expression that gives the same value as the one in the pattern is the one that represent the pattern.
(at n=2, expression must be equal to zero)
![\begin{gathered} -3n=-3(2)=-6 \\ -3n+6=-3(2)+6=0 \\ n+2=2+2=4 \\ 3n=3(2)=6 \\ 6n-3=6(2)-3=9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6ksf5k0qemvrc8ocmfzi0p45lclunlsn67.png)
At n=2 only one expression gave us zero.
So, the only expression that represent the given pattern is;
![B.-3n+6](https://img.qammunity.org/2023/formulas/mathematics/college/jlb85yql27079vsqhp81khnl40eq4crway.png)